Roze tijden : kansen en risico's voor de lesbische en homobeweging - Veenker, Janherman; Meulenbelt, Anja; Sanders, Stephan; Sandfort, Theo (Amsterdam : Schorer Boeken, 1998)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie